2019
DOI: 10.1007/s11676-019-00933-w
|View full text |Cite
|
Sign up to set email alerts
|

Biological significance of RNA-seq and single-cell genomic research in woody plants

Abstract: RNA-seq and single-cell genomic research emerge as an important research area in the recent years due to its ability to examine genetic information of any number of single cells in all living organisms. The knowledge gained from RNA-seq and single-cell genomic research will have a great impact in many aspects of plant biology. In this review, we summary and discuss the biological significance of RNA-seq and single-cell genomic research in plants including the single-cell DNA-sequencing, RNA-seq and single-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 113 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…The information content of an organism is recorded in its genomic DNA and expressed through transcription (Martin et al 2013;Tang and Tang 2019). In this study, publicly available transcriptome data for different tissues of ve Orchidaceae species were used to compare the expression levels of ARF genes in different tissues and developmental stages.…”
Section: Analysis Of Transcriptome Data For Orchid Arf Familymentioning
confidence: 99%
“…The information content of an organism is recorded in its genomic DNA and expressed through transcription (Martin et al 2013;Tang and Tang 2019). In this study, publicly available transcriptome data for different tissues of ve Orchidaceae species were used to compare the expression levels of ARF genes in different tissues and developmental stages.…”
Section: Analysis Of Transcriptome Data For Orchid Arf Familymentioning
confidence: 99%
“…Several studies showed that different plant cell types have unique molecular signatures that determine their differentiated functions (Ryu et al., 2019; Tang & Tang, 2019; Yuan et al., 2018). Advancement in proteomics analysis of small numbers of cells enabled the identification of cell type‐specific proteins with important roles in plant biological processes (Dembinsky et al., 2007; Petricka et al., 2012; Zhu et al., 2016).…”
Section: Commentarymentioning
confidence: 99%
“…However, to improve our understanding of plant cells as a system, there is a critical need to move toward studies focusing on individual plant cell types (Libault, Pingault, Zogli, & Schiefelbein, 2017). Recently, single‐cell RNA sequencing and genomics technologies have led to the discovery and classification of previously unknown cell states in plants (Ryu, Huang, Kang, & Schiefelbein, 2019; Tang & Tang, 2019; Yuan, Lee, Hu, Scheben, & Edwards, 2018). Yet, studies on proteins, as the major structural and functional determinants of cells, are often limited to whole tissue analyses, primarily due to the lack of a reliable and accurate cell‐type‐specific proteomics platform.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic data from thousands of single cells provide significant information that can be tapped using computational tools to understand molecular mechanisms of disease processes, host–pathogen interactions and mechanisms involved in cell differentiation, to understand the function of a single cell in various plant species. In future, the single‐cell DNA and RNA sequencing information will significantly help to explore rare transcripts in specific types of cells, facilitate rapid gene discovery and identification of novel biomarkers (Tang & Tang 2019).…”
Section: Future Directionsmentioning
confidence: 99%